Pedagogies of Black Eldership: Exploring the Impact of Intergenerational Contact on Youth Research. (3rd April 2017) - Lozenski, Brian D.
Abstract : This article examines the interactions between a collective of self-described "African American, " "multiracial, " and "African immigrant" high school youth researchers, and two African American community elders. Drawing from a year-long critical ethnographic study of the youth research collective, the author documents how pedagogies of Black eldership overlapped with youth participatory action research to open new possibilities for preparing youth as researchers. The study highlights how an out-of-school educational space afforded alternative pedagogical opportunities by specifically examining how pedagogies of Black eldership helped youth researchers historicize and politicize their research, pushing them to move from embodied knowledge to self-knowledge. Drawing from African-centered and critical theory, the study explicates aspects of the pedagogies of Black eldership. Without bounding these pedagogies, the author uses two narratives of teaching and learning to illustrate how intergenerational contact impacted the trajectory of the youth researchers. They transformed their research after meeting with the elders to be more introspective and examine how their worldviews were being constructed and influenced. The findings in this study serve as an impetus for further research examining the educational context of Black eldership and youth research.